Handbook of Florida Water Regulation: Soil and Water Conservation Districts - Michael T. Olexa; Tatiana Borisova; Jarrett Davis (EDIS)
This 2-page fact sheet written by Michael T. Olexa, Tatiana Borisova, and Jarrett Davis and published by the UF/IFAS Food and Resource Economics Department is part of a handbook designed to provide an accurate, current, and authoritative summary of the principal federal and Florida state laws that govern agriculture. This chapter provides an overview of soil and water conservation districts (SWCDs), explains their purpose and structure, and describes some of the agency partnerships SWCDs make. edis.ifas.ufl.edu/fe1017